Multi-purpose tree - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1994)
Trichantera gigantea, a member of the Acanthaceae family, is a multi-purpose tree which is known as \91Nacedero' in its native Colombia. It produces up to 100 tonnes of biomass per hectare per year and, although not a legume, appears to be...